Biopsicológigos and sociocultural factors as predictors of health promoting behavior of nursing students of the Adventist University of Chile - Aranda Sánchez, Daysi (2019)
Objective: To determine the biological, psychological and sociocultural factors of nursing students of theAdventist University of Chile are predictors of health promoting behaviors (CPS). Methodology: descriptivecorrelational quantitative cross-sectional study. Population: all first through fifth year of the undergraduate course.The sample was 137 students, selected by a random probability sampling, stratified. The instrument consistedof a semistructured questionnaire, level of lifestyle health promoter (EVPS) scale of perceived self-efficacy andself-esteem scale. Data were processed with SPSS 19.0. Results: biosocioculturales factors are not predictors ofhealth promoter behaviors in nursing students, as were evaluated at a confidence level of 95% however, the selfpsychological factor provided an association with promoting health behavior, as indicates the value X2 = 23.56, p= 0.00. and self-efficacy factor, has a direct and positive relationship with health promoting behavior, r = 0.30, p= 0.00. Conclusion: Self-esteem and self-efficacy are predictors of health promoting behavior in nursing studentsof the Adventist University of Chile.